Pengaruh komunikasi interpersonal pimpinan terhadap produktifitas dan kerja pegawai Pada kantor bupati kabupaten aceh jaya - Supriadi Supriadi; Martunis Yahya (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
Manajemen kepegawaian negeri sipil masih menyimpan banyak persoalan.  Kelebihan pegawai yang terjadi hampir di semua instansi pemerintahan telah menimbulkan berbagai masalah dalam manajemen kepegawaian negeri sipil di Indonesia terutama rendahnya kinerja dan produktivitas kerja. Dalam lingkungan kerja Kantor Bupati Kabupaten Aceh Jaya, pegawai saling berkomunikasi sesamanya sehingga terciptanya suatu interaksi dalam mengetahui berbagai masalah yang terjadi di lingkungan kerja terutama mengenai tanggungjawab, tujuan-tujuan yang diharapkan, kondisi yang terjadi dalam instansi dan sebagainya mengenai perubahan aturan kerja. Komunikasi interpersonal memberi kepercayaan yang kuat bagi pegawai sehingga mereka dapat menyatukan kembali lingkungan kerja yang sedang tidak kondusif. Kondisi ini akan berdampak terhadap produktivitas kerja pegawai. Berdasarkan ulasan tersebut penulis tertarik untuk mengadakan serangkaian penelitian ilmiah tentang pengaruh komunikasi interpersonal pimpinan terhadap produktivitas kerja pegawai pada kantor Bupati Kabupaten Aceh Jaya. Penelitian ini bertujuan untuk mengetahui sejauh mana pengaruh komunikasi interpersonal pimpinan terhadap produktivitas kerja pegawai pada Kantor Bupati  Kabupaten Aceh Jaya. Sampel dalam penelitian ini sebanyak 53 orang pegawai tetap (PNS). Teknik pengumpulan data digunakan angket dalam bentuk skala likert, metode analisa yang digunakan adalah analisis regresi linier berganda. Dari hasil analisis regresi linear berganda didapat model hubungan antara variabel terikat (Y) dengan variabel bebas (X1, X2) diperoleh model regresi yaitu Y= 2,799 + 0,587, X1 + 0,277, X2. Hasil analisa yang sudah diuji, pemerintahan pada Kantor Bupati Kabupaten Aceh Jaya juga sangat berpengaruh antara komunikasi interpersonal pimpinan terhadap produktivitas kerja pegawai yang memiliki persentase 88,6% dan juga memiliki signifikansi pengaruhnya yaitu 0,000. Effect of interpersonal communication of leadership to productivity and employee work At regent office of regency aceh jayaIn view of the various existing communication barriers, the achievements of Kluet Utara Sub-district Office employees can still be improved with the condition that the obstacles in the sub-district office are eliminated or reduced. Efforts to anticipate the development of business in the era of globalization, companies must prepare good management so as to realize the goals to be achieved. Employees should always cooperate with each other depending on mutual understanding through good communication execution. The focus in this study is only related to the open communication between the leadership with subordinates in the organization at the Office of the North Kluet Sub-district.               The theory used is Johari Window Theory and Theory X and Y. Johari Window Theory is a simple and useful tool in illustrating and increasing self-awareness and understanding with individuals in a particular group. This model also works in improving relationships between groups that at once illustrate the process of giving and receiving feedback. Theory X and Y are based on assumptions about employees or employees and how to motivate them               Approach This research uses qualitative research methods. Qualitative research methods basically explain the way that will be taken by a researcher in the research process. The location of this research is Sub-District Office of North Kluet Subdistrict which is located in Simpang Empat National Road, North Kluet Sub-district, South Aceh District. Informants in this study amounted to 5 people. Data collection used in this research is observation, in-depth interview and documentation. Data is processed by data reduction, display data, take conclusion and verification.               The results obtained are: 1). Disclosure of communication between leaders and subordinates in the organization "(study at the office of North Kluet Sub-district of South Aceh) has been going well as expected. The effort to create open communication between the leaders to the subordinates goes well in the Kluet Utara District Office of South Aceh, the head of the Kluet Utara District Office of South Aceh holds meetings and deliberations with employees and provides information through internal communication pattern methods and internal meetings with employees in the agency. 2). Barriers in carrying out its functions such as unsuitable bonuses from superiors as an appreciation of achievements gained.